Transformation of Ade' Pitue Leadership Values in Government in Bone District - ., Bakhtiar; ., Mustaring; Sudirman, Muh.; Dwiputra, Rahyudi (KnE Social Sciences, 2024)
Apart from being influenced by the leadership system, the leadership style is also influenced by the legacy of sociocultural values that were good practices of past administrations. Ade’ Pitue is a system of government that was implemented when Bone was still a monarchical form of government, considered the best model of government in its time. This study aims to obtain an overview of: (1) Leadership values in Ade’ Pitue, (2) Forms of leadership in modern government, and (3) Factors that influence the transformation of Ade’ Pitue leadership values in government. The method used is descriptive qualitative. Data were collected through literature study and analyzed through data reduction, data display, verification, and drawing conclusions. The results of the study show: (1) Leadership values in Ade’ Pitue, are Macca (intelligent), Lempu (honest), Warani (brave), Getteng (steadfast) on the truth (tongeng); (2) The form of leadership in modern government as a transformation for the values of Ade’ Pitue leadership is the application of representation of the people’s interests through the customary council (Ade’ Pitue) based on the results of deliberations; (3) The factors that influence the transformation of Ade’ Pitue leadership values in government are the Siri’ na Pacce culture. In addition, according to Kajalilddong, factors for enlarging the kingdom are: (1) Seuwani, temmatinroi matanna Arung Mangkau’E mitai munrinna gau’e, which means that the king’s eyes are not closed thinking about the consequences of all actions; (2) Maduanna, maccapi Arung Mangkau’E duppai ada, meaning the king must be smart in answering words, (3) Metelunna, maccapi Arung Mangkau’E mpinru ada, which means that the king must be good at making words or answers, and (4) Maeppa’na, tettakkalupai surona mpawa ada tongeng, which means that the four kings don’t forget to convey the correct words. Keywords: Ade’ Pitue, governance, leadership, transformational, Values